Kur’an- ı Kerim’de helak kavramı - Çimen, Abdullah Emin (My University, 2001)
The name of thesis is “The term of destruction (Helak) in the Quran”. İts contains thre parts: İn the first chapter. I studied the term of Helak (destruction) in the Quran. In the second chapter. I studied the individuals and communities that destroyed pre- İslamic ages. In the third chapter. I tried to analyse the reasons typies and forms of destruction. In this chapter I studied the relation between the term of helak (destruction) and sunnetullah (the law of God). I studied the social change from point of helak (destruction) and studied ways of avoiding from helak (destruction). In the conslusion, I summarized and evaluted the results of these studies.
Keywords: Din; İslam Dini; Kur’an ve Kur’an İlimleri; Kur’an-ı Kerim; Tefsir